Modifikasi Algoritma Edmonds Karp untuk Menentukan Aliran Maksimum Pada Jaringan Distribusi Air PDAM (Studi Kasus Jaringan Telaga Sari PDAM Giri Menang Mataram) - Hotimah, Husnul; Bahri, Syamsul; Awalushaumi, Lailia (University of Mataram, 2023)
Clean water is the main and basic need for humans which is of concern to the government. Distribution network system is a very important part to delivering water to all consumers. The lack of water discharge distribution in several areas, especially at the end of the pipeline service, is cause by not optimal water distribution, the flow rate of sorce and leak in pipeline effect. This research has to analyze the optimal network model and determine the maximum flow rate from the PDAM pipeline using modified Edmonds Karp algorithm. Modified Edmonds Karp algorithm is a method for calculating maximum flow of a network. Based on analysis of modified Edmonds Karp algorithm there is a less efficient us of pipe in PDAM network and result of maximum flow from the network is 202,30 liter/second. This means it can be adding flow discharge to the water distribution pipe by PDAM for expedite the flow to consumer with the addition of flow should not exceed 202,30 liter/second.